Correlation Between Joint-Position Sense, Peroneal Strength, Postural Control, and Functional Performance Ability in Patients With Chronic Lateral Ankle Instability. (August 2019) - Cho, Byung-Ki; Park, Ji-Kang
Background: The first aim of this study was to evaluate the side-to-side difference of joint-position sense, peroneal strength, postural control, and functional performance ability in patients with chronic lateral ankle instability. The second aim was to identify the correlation between various components contributing to the functional ankle instability (FAI). Methods: Thirty-five patients to be scheduled for the modified Broström procedure for chronic ankle instability were analyzed. Joint-position sense and peroneal strength were measured with an isokinetic dynamometer. Postural control ability was evaluated using the modified Romberg test. The functional performance test consisted of the 1-leg hop test, 6-meter hop test, and cross 3-m hop test. Spearman's correlation coefficient ( r ) was calculated to determine the linear association between the individual components of the FAI. Results: Except for the 6-m and cross 3-m hop tests, most examination tools for the FAI demonstrated significant side-to-side differences compared with the unaffected ankle. Spearman's correlation analysis revealed that individual components (joint-position sense, peroneal strength, postural control, and functional performance ability) of the FAI were significantly associated with one another, except between peroneal strength and postural control ability ( r = 0.21, P = .195). Conclusion: Joint-position sense, peroneal strength, postural control ability, and 1-leg hop test demonstrated significant side-to-side differences in patients with chronic lateral ankle instability. Individual components contributing to the FAI were significantly correlated with one another, except between peroneal strength and postural control ability. Postural control evaluation using the modified Romberg test could substitute for dynamometer testing, with convenience and economic advantage. Level of Evidence: Level IV, prospective case series.